Analysis ground electric field strength propagates beneath 132 KV power lines - Baharom, Md Nor Ramdon; Zainal, Zainab; Saufi, Muhammad; Ishak, Mohd Taufiq; Ullah, Irshad (Penerbit UTHM, 2020)
The National Power Grid consists of transmission lines that crisscrossing the country carrying bulk of electrical energy to the consumers. The primary transmission lines in Malaysia carrying 132 kV, 275 kV and 500 kV system voltage and mainly delivered by overhead line tower between the main generation/intake substations. Among them, 132 kV lines are the oldest, populating the grid and erected mainly alongside routes closer to the development area. In some cases, they can be seen crossing next/ near to the public building or even having a development underneath the lines (i.e. parking are, shelter, illegal shelter, crops area etc.).